High Value Phycotoxins From the Dinoflagellate Prorocentrum - Camacho-Muñoz, Dolores; Praptiwi, Radisti A.; Lawton, Linda A.; Edwards, Christine (Frontiers in Marine Science, 2021)
Marine dinoflagellates produce chemically diverse compounds, with a wide range of biological activity (antimicrobial, anticancer, treatment of neurodegenerative disease along with use as biomedical research tools). Chemical diversity is highlighted by their production of molecules such as the saxitoxin family of alkaloids (C10H17N7O4 – 299 g/mol) to the amphipathic maitotoxin (C164H256O68S2Na2 – 3,422 g/mol), representing one of the largest and most complex secondary metabolites characterized. Dinoflagellates, are most well-known for the production of red tides which are frequently toxic, including okadaic acid and related dinophysistoxins, which are tumor promoters. The mode of action for these phycotoxins, is by specific inhibition of protein phosphatases, enzymes essential in regulation of many cellular processes. Hence, these compounds are being used for vital cell regulation studies. However, the availability of useful amounts of these compounds has restricted research. Chemical synthesis of some compounds such as okadaic acid has been investigated, but the complexity of the molecule resulted in many lengthy steps and achieved only a poor yield. The use of naturally occurring phytoplankton has been investigated as a potential source of these compounds, but it has been shown to be unreliable and impractical. The most practical option is large scale culture with down-stream processing/purification which requires specialist facilities and expertise. This review, describes the biotechnological potential of these organisms and the challenges to achieve useful yields of high quality phycotoxins using Prorocentrum spp. as an example to produce okadaic acid.